Variation in the nitrogen isotopic composition of amino acids in benthic foraminifera: Implications for their adaptation to oxygen‐depleted environments. (25th July 2015) - Nomaki, Hidetaka; Chikaraishi, Yoshito; Tsuchiya, Masashi; Toyofuku, Takashi; Suga, Hisami; Sasaki, Yoko; Uematsu, Katsuyuki; Tame, Akihiro; Ohkouchi, Naohiko
Abstract: We evaluated nitrate utilization by benthic foraminifera at the redox boundary around the sediment‐water interface by examining the stable nitrogen isotopic composition ( δ 15 N, ‰ vs. AIR) of amino acids. Five foraminiferal species collected from bathyal Sagami Bay (water depth, 1430 m) in three different sampling seasons were analyzed by determining the δ 15 N values of amino acids from whole cells and those in test (shell) proteins remaining after H2 O2 treatment. The δ 15 N values of phenylalanine fell within a narrow range (typically 1–3‰) in the test proteins of all five species, but the whole‐cell δ 15 N values of phenylalanine were substantially different from those of the test proteins in two species, Globobulimina affinis (by 6.3‰) and Uvigerina akitaensis (by 4.5‰). These differences in the δ 15 N values of amino acids suggest that these species utilize nitrate in their cells probably for nitrate respiration (i.e., denitrification) to adapt to oxygen‐depleted environments, as was previously observed in the shallow water benthic foraminifera Ammonia sp. Apparent trophic positions determined using the δ 15 N values of amino acids also differed between whole cells and tests in G. affinis, U. akitaensis, and Ammonia sp., perhaps because they have different microbial associations, as observed by cellular ultrastructural analysis. These differences in nitrate utilization and microbial associations among benthic foraminifera suggest that foraminifera adapt in diverse ways to conditions in dysoxic to anoxic sediments.